Analisis dan Faktor yang dapat Mempengaruhi Pencairan dan Pelunasan Pinjaman Kredit Usaha Rakyat - Juni Sasmiharti (LITERATUS, 2022)
KUR loans are designed for small and medium-sized businesses that are economically viable but are not yet eligible for traditional bank financing. Since 2008, the number of KUR in BRI Unit X has decreased sharply due to high credit arrears. This poses a lot of problems for people who depend on this unit for their livelihoods. This research uses research data collected from secondary sources such as bank data, which is then deepened by conducting interviews with selected debtors and tracing various relevant literature sources. Data analysis includes qualitative and quantitative analysis. This study seeks to identify the factors that contribute to the successful completion and return of KUR. The study found that various business factors such as turnover, net profit, type of business, proposed credit, and collateral value all had a significant effect on the likelihood of success of the KUR. There are several factors that can affect the repayment rate of the KUR loan, such as the gender of the borrower, the level of education, the repayment term, and the monthly installment payment. and credit interest.